Kemiskinan dalam Novel Di Kaki Bukit Cibalak Karya Ahmad Tohari - Dewi Ratnaningsih (Universitas Muhammadiyah Kotabumi, 2017)
Literature is the most optimal meda to express idea of a writer. The ideas could be on the form of feedback, critic, satire, or the reaction. The literature is the mirror of society life, so that there are some life point of views included on the novel